2018
DOI: 10.1016/j.neuropharm.2018.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the TREK-1 potassium channel via riluzole to eliminate the neuropathic and depressive-like effects of oxaliplatin

Abstract: Neurotoxicity remains the most common adverse effect of oxaliplatin, limiting its clinical use. In the present study, we developed a mouse model of chronic oxaliplatin-induced neuropathy, which mimics both sensory and motor deficits observed in patients, in a clinically relevant time course. Repeated oxaliplatin administration in mice induced both cephalic and extracephalic long lasting mechanical and cold hypersensitivity after the first injection as well as delayed sensorimotor deficits and a depression-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 71 publications
4
50
0
Order By: Relevance
“…Moreover, riluzole decreases the viability of a human colorectal cancer cell line in vitro and inhibits polyp development in vivo. These data confirm the important role of TREK-1 and TRAAK in CIPN [82,83].…”
Section: K V Channelssupporting
confidence: 83%
“…Moreover, riluzole decreases the viability of a human colorectal cancer cell line in vitro and inhibits polyp development in vivo. These data confirm the important role of TREK-1 and TRAAK in CIPN [82,83].…”
Section: K V Channelssupporting
confidence: 83%
“…They will be revised with particular attention paid to the hypothesis leading to the study, to the trial strengths and weaknesses, and to the outcome measures proposed to test the efficacy of the neuroprotective approach. In OHP-treated animals, riluzole prevents the excessive accumulation of glutamate [34], and recently it was evidenced the benefit of riluzole for sensorimotor and painful disorders of the peripheral nervous system, preventing OHP-induced peripheral nerve functional and morphological alterations, as well as related OHP-induced comorbidities [35]. It has been postulated that riluzole could exert its neuroprotective action through interaction with potassium channels of the K2P family (TREK, TRAAK) [36,37].…”
Section: Prevention and Treatment Of Ohp-related Peripheral Neurotoximentioning
confidence: 99%
“…Intrathecal injection of miR-183 alleviated pain in rat model of CCI and downregulated TREK-1 expression (Shi et al, 2018). Recently, it was reported that TREK-1 modulator riluzole prevents both sensory and motor deficits in neuropathic pain induced by the chemotherapy drug oxaliplatin (Poupon et al, 2018). Nevertheless, conclusions drawn by this paper are not totally convincing because authors only consider riluzole as an activator and do not take into account its inhibitory effects.…”
Section: Trek-1 Channelmentioning
confidence: 99%